Band gap enhancement in periodic frames using hierarchical structures. (1st May 2021) - Dal Poggetto, Vinícius F.; Bosia, Federico; Miniaci, Marco; Pugno, Nicola M.
Graphical abstract: Highlights: A 1D-periodic phononic crystal is designed using a spider web-inspired architecture. The resulting structure made of spatial frames has torsional and bending band gaps. Both square and hexagonal 2D-periodic lattices can be formed hierarchically. The resulting plane phononic crystals show out-of-plane complete band gaps. Hierarchy allows to open and widen band gaps with respect to nonhierarchical frames. Abstract: The quest for novel designs for lightweight phononic crystals and elastic metamaterials with wide low-frequency band gaps has proven to be a significant challenge in recent years. In this context, lattice-type materials represent a promising solution, providing both lightweight properties and significant possibilities of tailoring mechanical and dynamic properties. Additionally, lattice structures also enable the generation of hierarchical architectures, in which basic constitutive elements with different characteristic length scales can be combined. In this work, we propose 1D- and 2D-periodic phononic crystals made of spatial frames inspired by a spider web-based architecture. Specifically, hierarchical plane structures based on a combination of frames with a variable cross-section are proposed and exploited to open and enhance band gaps with respect to their non-hierarchical counterparts. Our results show that hierarchy is effective in broadening existing band gaps as well as opening new full band gaps in non-hierarchical periodic structures.